2017
DOI: 10.31351/vol21iss1pp56-60
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Levels of Tumor Necrosis Factor-Alpha and Antioxidant status in Different Stages of Malignant Prostate Cancer Patients in Iraq

Abstract: Chronic inflammation can induce proliferative events and posttranslational DNA modifications in prostate tissue through oxidative stress. The present study was designed to evaluate the changes in serum levels of TNF-α, malomdialdehyde (MDA) and total antioxidant status (TAS) patients with different stages of malignant prostatic cancer (PCa) and benign prostatic hyperplasia (BPH). One hundred males (age range of 58-72 years) with different stages of malignant PCa were recruited from the Radiotherapy and Nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is clear from the results of the current study that the patients are oxidatively stressed, as they have a high level of malondialdehyde and a decrease in the level of glutathione in the blood serum. The studies also indicated that the level of total antioxidants varies with the degree of disease, whether for patients with PC or patients with BPH, so the study suggested evaluating the level of TAC to monitor the progress of the disease (45) .…”
Section: Figure (3)mentioning
confidence: 99%
“…It is clear from the results of the current study that the patients are oxidatively stressed, as they have a high level of malondialdehyde and a decrease in the level of glutathione in the blood serum. The studies also indicated that the level of total antioxidants varies with the degree of disease, whether for patients with PC or patients with BPH, so the study suggested evaluating the level of TAC to monitor the progress of the disease (45) .…”
Section: Figure (3)mentioning
confidence: 99%
“…During higher oxidative stress, the antioxidant system of host cells and tissues could not counteract over produced ROS due to which excess ROS react with DNA, protein consequently leading to the progression of chronic inflammatory related diseases. In natural products, there are many compounds which possess antioxidant property therefore these can prevent oxidative stress and prevent damage to cells caused by foreign xenobiotics and thereby balancing oxidative stress level and prevent progression of inflammatory diseases [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%